Synergizing Traditional Knowledge and Sustainable Local Practices for Enhancing Coastal Resource Education and Management- an Indian Scenario - Tilak, J. Logamanya; Nesakumari, C. Sheeba Anitha; Jesudasan, R.W. Alexander; Thirunavukkaras , N. (Silliman Journal, 2022)
The diverse marine and coastal habitats in India harbor a wide range of biodiversity which has not been fully understood due to logistic constraints. The variety of coastal ecosystems along the Indian coastline measuring 8,129 km encompassing nine maritime states and four union territories include estuaries, lagoons, mangroves, backwaters, and coral reefs. The marine floral and faunal diversity is immense that India stands third in fish production and second in aquaculture in the world. This vast coastline, which has such rich coastal resources, has always been under threat, atleast in the recent past due to reasons, viz. nature, anthropogenic factors, and urbanization. These factors have contributed to the loss in biodiversity endangering few species to the brink of extinction. As a part of the conservation campaign for coastal resource management in India, traditional knowledge that helped in sustainable fishery has to be revived through synergizing the activities of the academicians, policy makers, and NGOs to draft a proposal for an effective and successful coastal resource management. Inculcating the need for coastal resource management in the minds of future generation would warrant the introduction of this focal point at different levels of education, and the wealth of traditional knowledge of the fisherfolk of Pulicat Lake in Tamil Nadu would be an added feature on this subject.